Investigation of ZnO Nanotetrapods at different evaporation temperatures by thermal-CVD method for OLED applications / Najwa Ezira Ahmed Azhar...[et al.] - Ahmed Azhar, Najwa Ezira; Shariffudin, Shafinaz Sobihana; Rusop, Mohamad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Organic semiconductors have been discovered for various applications such as in organic light-emitting diodes (OLEDs). Zinc oxide (ZnO) nanostructures have been discovered and received much attention in various applications such as in organic light-emitting diodes (OLEDs), solar cells, sensors and so on. The metal oxides such as ZnO provide an interesting alternative for conventional metal that as low work function as electron injection layer in OLEDs. This study focuses on the synthesization of ZnO nanotetrapods at different evaporation temperature using double furnace thermal chemical vapor deposition (CVD). The ZnO nanotetrapods was produced from synthesized of Zn powder (≥99.9% purity, Sigma Aldrich). From X-Ray Diffraction (XRD) pattern, it is confirmed that (101) diffraction peak successful growth nanotetrapods structure. The ZnO (101) diffraction peak indicates that the nanotetrapods exhibit good crystalline quality. The ZnO nanotetrapods were characterized using field emission scanning electron microscope (FESEM). It shows that the diameter size of ZnO nanotetrapods range in nanometer. Meanwhile, the length of nanotetrapods was around 1.15μm. Photoluminescence of nanotetrapods shows the highest intensity for sample temperature of 750oC at visible emission. It can be seen that the highest at visible emission was due to the oxygen vacancy or Zn interstitial effects. These properties will provide better performances and it is suitable for optoelectronic device especially in OLED